Strategi Pengembangan Karir Melalui Organization Learning di PT ACE Hardware Indonesia - Nurulita, Darliani; Hidayat, Arief; Miranda, Ade; MP, Eva Linandra; Mayola, Putri; Fandani, Mona; AP, Yuana Cita; Sikki, Nurhaeni (Universitas Pahlawan Tuanku Tambusai, 2024)
In development rapid technology and the growth of knowledge-based society require companies to continue to provide training and learning in accordance with developments that have occurred. Various programs for developing human resources and technology provide an illustration that PT Ace Hardware Indonesia, Tbk is a learning organization. The aim of this research is to optimize career development strategies using the organizational learning method. This research uses qualitative methods (case study). Research data collection was carried out by researchers using interview, observation and documentation methods. The research obtained data sources from middle-up employees (supervisors, deputy store managers and store managers) as much ten person as primary data sources. Based on the research results above using tehnik Analisis SWOT, the researcher concludes that PT Ace Hardware Indonesia, Tbk has implemented a career development strategy, what is needed now is strategy optimization through the organizational learning method. In this research, there are five indicators which are divided into two groups of internal factors, namely personal skill indicators (personal mastery), mental models, shared vision, while the external factor group is team learning indicators, and systems thinking, research results show that the implementation has been maximized but requires optimization of strengthening strategies to utilize opportunities with existing strengths (SO strategy) in quadrant I which means aggressive to take advantage of opportunities and optimize strengths, by implementing career development strategies through superior motivation and teamwork to expand lines. managerial knowledge, improving HR capabilities through the KLA academy method which is easy for all employees to access and utilizing facilities and infrastructure (technological support such as intranet networks) in developing the KLA academy system Keywords: Career development; EFAS; IFAS; Organization Learning